Body Dissatisfaction and Depressive Symptoms in Youth: The Mediating Role of Self-Criticism - Rodrigues da Silva, Diana; Mwangi, Grace (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the relationship between body dissatisfaction and depressive symptoms among adolescents, with a particular focus on the mediating role of self-criticism.Methods and Materials: A descriptive correlational design was employed, with 388 adolescents recruited from educational institutions in Kenya. The sample size was determined using the Morgan and Krejcie table to ensure representativeness and statistical power. Participants completed standardized self-report instruments measuring body dissatisfaction, self-criticism, and depressive symptoms. Data analysis was conducted in two stages. Pearson correlation coefficients were calculated using SPSS version 27 to examine the associations between body dissatisfaction, self-criticism, and depressive symptoms. Structural Equation Modeling (SEM) was subsequently performed in AMOS version 21 to test the hypothesized mediating role of self-criticism in the link between body dissatisfaction and depressive symptoms. Model fit was assessed using multiple indices, including the Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), and Root Mean Square Error of Approximation (RMSEA).Findings: Pearson correlations indicated significant positive associations between body dissatisfaction and depressive symptoms (r = .46, p < .001), between body dissatisfaction and self-criticism (r = .41, p < .001), and between self-criticism and depressive symptoms (r = .52, p < .001). SEM results supported a partial mediation model, demonstrating that self-criticism significantly mediated the relationship between body dissatisfaction and depressive symptoms (indirect effect = .21, p < .001). The model demonstrated good fit (χ²/df = 2.14, CFI = .94, TLI = .92, RMSEA = .051), confirming the robustness of the mediational pathway.Conclusion: These findings highlight the critical role of self-criticism in linking body dissatisfaction to depressive symptoms among adolescents.